Dynamics of Perceived Positive Changes and Indicators of Well-Being Within Different Phases of the COVID-19 Pandemic - Büssing, Arndt; Rodrigues Recchia, Daniela; Dienberg, Thomas; Surzykiewicz, Janusz; Baumann, Klaus (Frontiers in Psychiatry, 2021)
Background: During the COVID-19 pandemic, people reported about fears, depressive states, and phases of loneliness. However, there have also been positively experienced changes in terms of awareness of nature, reflection of life, more intensive relationships, meaningful digital media usage to connect with others, and interest in spirituality. We were interested in the dynamics of these indicators directly after the first lockdown, the summer months and during the second wave of the pandemic with its second lockdown, and how they relate to the perceived restrictions, fears, and worries. Method: Survey with standardized questionnaires, i.e., Perceived Changes Questionnaire, WHO-Five Well-being Index, Brief Multidimensional Life Satisfaction Scale, Awe/Gratitude scale. Participants were categorized as cohort 1 (June 2020; n = 1,333), cohort 2 (July to September 2020, n = 823), and cohort three (October 2020 to January 2021, n = 625). Results: Participants perceived changes in specific attitudes and behaviors, which have impacted their well-being and life satisfaction. Compared to their experiences directly after the first wave of the pandemic (cohort 1), well-being (Hedge's g = 0.83) and life satisfaction (g = 0.63) decreased during the second wave (cohort 3) and participants' stressors increased (g = −0.94). At the same time, positive perceptions such as Nature/Silence/Contemplation (g = 0.67), Spirituality (g = 0.62), Relationships (g = 0.55), and Digital media usage declined (g = 0.31), but not Reflections on life (g = −0.03). In cohort 3, the proportion of persons relying on their faith as a strong hold was declining also in nominally religious persons. Awe/Gratitude was among the best predictors of perceived positive changes, indicating a resource which is nevertheless declining during the second wave of the pandemic (g = 0.60). Conclusions: Several perceptions, attitudes, and behaviors have changed, particularly during the second wave of the pandemic, which had a strong influence on psychological health. Although Awe/Gratitude was confirmed as the best predictor of perceived positive changes, this resource may not buffer against the negative outcomes of the pandemic but helps to recognize the still positive aspects in life. There is a need for new and not yet defined public health communities that could focus on persons which are affected in their physical, mental, social, and spiritual health and well-being due to the pandemic.